Why are children absent from preschool? A nationally representative analysis of Head Start programs - Purtell, Kelly M.; Ansari, Arya (Frontiers in Education, 2022)
Children who are absent from school, including preschool, do not make the same academic gains as their non-absent peers. Despite the harmful implications of school absences, we know little about what predicts absenteeism among preschool-attending children. In this study, we used the Family and Child Experiences Study (2009), a nationally representative sample of Head Start attendees (n = 2,842), to test the associations between a comprehensive set of child, family, and center factors, and children’s levels of absenteeism across the preschool year. Our findings highlight the multi-faceted nature of absenteeism and suggest that family necessity and family routines may both play a role in preschoolers’ absenteeism. Additionally, our findings point to a number of center-level characteristics, including outreach strategy and classroom quality, which may reduce children’s absenteeism.